Pola Komunikasi Ketua RW 007 Kelurahan Rawamangun dalam Meningkatkan Partisipasi Warga pada Program Bank Sampah - Fakhri Akbar, Achmad; Triartanto, Yuda; Tri Susanto, Teguh (UNIVERSITAS SERAMBI MEKKAH, 2024)
Communication serves as a crucial tool for humans, facilitating information exchange and impacting social life significantly. The Waste Bank program in RW 007 aims to enhance environmental cleanliness through a waste-saving initiative, involving 38 out of 994 residents. This study investigates the communication strategies of RW 007's Chair to boost participation in the Waste Bank program. Employing a descriptive qualitative method, data was gathered via observation, interviews, and documentation. Analysis involved data reduction, presentation, and conclusion drawing. Findings reveal the Chair's communication pattern has three effects: Cognitive (improving understanding of the program's importance), Affective (cultivating residents' care for the environment by reducing landfill burdens), and Behavioral (establishing a habit of collecting plastic bottles for exchange). Supporting factors include governmental backing, mutual reminders among residents, and the active RW 007 Residents' Communication Forum WhatsApp Group. Conversely, challenges include fluctuating citizen involvement and accessibility issues in certain areas.